(c+1/c^{2})2

= (c+1/c)(c+1/c)

= c^{2}+1/c^{2}+1/c^{2}+1/c^{4}

=c^{2}+2/c^{2}+1/c^{4 }=c^{6}+2c^{2}+1

Printable View

- June 2nd 2012, 08:33 PMzbest1966Simplify
(c+1/c

^{2})2

= (c+1/c)(c+1/c)

= c^{2}+1/c^{2}+1/c^{2}+1/c^{4}

=c^{2}+2/c^{2}+1/c^{4 }=c^{6}+2c^{2}+1 - June 2nd 2012, 09:33 PMrainbowoblivionRe: Simplify
Are you just wanting someone to double check your work?

- June 2nd 2012, 10:00 PMProve ItRe: Simplify
- June 3rd 2012, 06:58 AMSorobanRe: Simplify
Hello, zbest1966!

Wow! . . . Can you make a few more errors ... please?

Quote:

. . . Where is the ?

. . . This is terribly wrong!

. . . Well, you added correctly ...

. . . What happened to the denominator?

I will assume that the problem is: .

We have: .

"FOIL": .

. . . . .

. . . . .

. . . . .

- June 3rd 2012, 07:01 AMWilmerRe: Simplify
...or [(c + 1) / c^2]^2 ?

Video: How to Use Parentheses in Equations | eHow.com